Towards a Public-Organization Conversational Framework of Reputational Influence: a Grounded Theory Study - Wan Noordin, Wan Norbani (Auckland University of Technology, 2013)
Reputation is posited as a narrative and communicative construct that is developed through conversations with publics (Aula, 2011) and among publics (Mahon, 2002; Mahon & Wartick, 2003). However, to date research in the field of reputation has been mostly business and management focused and defined. The absence of a fully explicated definition (with an emphasis on reputation) in public relations theory and research limits theory building in public relations.The aim of this study is to propose a substantive model of reputation from a public relations perspective by examining how online conversations impact organizational reputation in four social media (discussion sites, Twitter, Facebook and YouTube) conversations about four organizations (Apple, BP, Nokia and Toyota). It analyzes in detail how conversations between publics affect an organization's reputation. A grounded theory approach was employed which allowed for better understanding of how concepts of reputation are socially constructed through issues, values, and concerned conversations between publics about their organization. The findings suggest that the central tenet of an organization's reputation is the management of public relationships which can lead to positive, strong and resilient reputations. Further, the cultivation of relationships with publics through social media conversations is important to the longevity and reputation of an organization. This study proposes the Publics Conversational Model of Reputational Influence which blends three important concepts to the scholarship, which are: a) public relationship, b) reputation as a sum of perceptions that is derived from stories and conversations and inherently comparative and c) publics and their formation in online conversations. Building on the fundamental premise that quality relationships are the key–precursor of a favorable reputation (Fombrun, 1996), the model proposes the concept of publics–organization relationships (POR). It explains the process of reputation formation, its landscape and key constructs.
Keywords: Reputation; Public relations; Social media; Conversations between publics; Grounded theory